The Potential of Isoniazid Derivatives as Anti-Tuberculosis Drugs targeting 6MA8: In Silico Study - Muhammad Yogi Saputra; Atthar Luqman Ivansyah; Nabila Aprilia Maharani; Rahmat Kurniawan; Refsya Azanti Putri; Irham Fauzi Abshar (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2025)
Tuberculosis (TB) is a contagious disease caused by Mycobacterium tuberculosis. Isoniazid, a synthetic antimicrobial agent, remains one of the most crucial first-line medications in TB therapy. Enhancing TB treatment strategies can be achieved through structural modifications of existing drugs. This study investigates the potential of isoniazid derivatives as anti-tuberculosis agents targeting the CYP3A4 protein complexed with a small-molecule inhibitor (PDB ID: 6MA8) and evaluates their toxicity profiles using in silico methods. The ligands analyzed include isoniazid derivatives 1–5, with isoniazid as a reference compound and protoporphyrin as the native ligand. The structure of ligands was prepared using Avogadro software and optimized with ORCA software. The crystal structures of 6MA8 were retrieved from the PDB database and further validated using YASARA. In silico methods such as molecular docking and ProTox prediction were employed to evaluate the potential of these isoniazid derivatives as anti-TB drugs. The interactions were visualized using Biovia Discovery to assess the interaction between the isoniazid derivatives and the receptor. The results showed derivative 4 exhibited the lowest binding affinity (-71.56 kcal/mol) compared to isoniazid (-65.90 kcal/mol), derivative 1 (-63.65 kcal/mol), derivative 2 (-67.01 kcal/mol), derivative 3 (-67.37 kcal/mol), derivative 5 (-69.02 kcal/mol), and native ligand (-182.68 kcal/mol). Biovia Discovery Studio simulations indicated that the isoniazid derivatives interacted with 6MA8 via conventional hydrogen bonds, carbon-hydrogen bonds, and other interactions. The toxicity analysis showed that the derivatives had safe LD50 values, supporting their safety profiles. These results suggest that isoniazid derivatives have promising potential as anti-tuberculosis agents targeting 6MA8.